2016
DOI: 10.1007/s00068-016-0674-5
|View full text |Cite
|
Sign up to set email alerts
|

The survival impact of plasma to red blood cell ratio in massively transfused non-trauma patients

Abstract: In non-trauma patients undergoing massive transfusion, increasing FFP:PRBC ratio was associated with improved survival. A ratio >1:3 significantly improved survival probability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…25 Although the role of damage-control resuscitation outside of traumatic injury is unknown, prompt hemorrhage control is likely to be an important component of care. 26,27 4. The protocol shall consider the available resources at the institution.…”
Section: Resultsmentioning
confidence: 99%
“…25 Although the role of damage-control resuscitation outside of traumatic injury is unknown, prompt hemorrhage control is likely to be an important component of care. 26,27 4. The protocol shall consider the available resources at the institution.…”
Section: Resultsmentioning
confidence: 99%
“…Existing studies also demonstrated benefits of MTP implementation in non-trauma patient population. However, a high ratio of plasma to pRBC is not associated with an improved death rate in certain studies [9][10][11][12][13]15]. In our retrospective review of hospital-wide MTP implementation involving non-trauma patients with severe hemorrhage, we tried to investigate the effect of implementation by comparing patients of the pre-MTP implementation period and the post-MTP implementation period.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted with pediatric patients reported that mortality was not significantly different between MTP group and non-MTP group [14]. However, another study reported the opposite results, that increasing the plasma to pRBC ratio was associated with improved survival in nontrauma patients [13]. T MTP in non-trauma patients, we aimed to investigate the clinical effect of the implementation of massive transfusion protocol in non-trauma patients.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Availability of MTP has led to its utilisation in patients with major bleeding from non-traumatic causes such as aneurysm rupture, post-partum haemorrhage and gastro-intestinal bleeding. Recent studies have evaluated the impact of MTP activation on blood product utilisation and patient mortality [11,13,14]. We previously reported that MTP use between 2008 and 2011 increased plasma, platelet and cryoprecipitate per patient but the median number of RCs transfused or hospital mortality did not change [15].…”
Section: Massive Transfusion Protocolsmentioning
confidence: 99%